TECHNOLOGY OF CREATIVE FORMATION STUDENTS 'PERSONALITIES IN EDUCATIONAL PROCESSES (Pedagogy of Higher and Secondary Education, 2000)
The conditions of the educational process and the conditions of its organization form methods, which help to develop the Creative qualifies of a person a covered in the article.